Effect of abiotic feeding factors on mineral metabolism in bulls - Ryazanov, Vitaly; Duskaev, Galimzhan; Kolpakov, Vladimir; Kazakova, Tatyana; Marshinskaia, Olga; Ruchay, Alexey (Agriculture and Natural Resources, 2025)
Importance of the work: The study of the combined effects of the wormwood plant (Artemisia absinthium L.) and trace elements is crucial for understanding their impact on cattle metabolic systems. Objectives: To evaluate the effect of Artemisia absinthium L. and cobalt chelate compounds on the metabolic parameters and mineral metabolism of bulls. Materials and Methods: The study was undertaken at the Federal Scientific Center for Biological Systems and Agrotechnology of the Russian Academy of Sciences using a sample of 16 Kazakh bulls (white-headed breed, aged 13-14 mth). The experiment used a 4 × 4 Latin square design, comprising four repetitions with four bulls per group, across 17 d periods (10 d of adaptation and 7 d of sampling). Blood samples were collected during each sampling period to determine biochemical indicators and trace elements. Biochemical analyses were performed using an automatic biochemical analyzer, while trace element levels in serum were assessed using inductively coupled plasma spectrometry. Results: Alterations in feeding conditions significantly affected the metabolism of the Kazakh white-headed bulls. During the experimental period, incorporating a plant-based feed supplement derived from Artemisia absinthium L. was an optimal strategy for enhancing metabolic processes and promoting growth in the bulls. The combined introduction of wormwood and cobalt compounds into the diet resulted in increases in the levels of cobalt (Co) by 67% (p = 0.002), chromium by 80% (p = 0.004) and selenium by 12% (p = 0.05). Furthermore, when Co compounds were administered alone, there was a notable increase in Co levels by 100% (p = 0.002), accompanied by a decrease in iodine levels by 33% (p = 0.007). Additionally, groups receiving wormwood supplements had increased concentrations of heavy metals (nickel and lead) exceeding 10%. Main finding: Feeding a plant-based additive comprising Artemisia absinthium L. and cobalt chloride (CoCl₂) compounds was optimal for cattle. This combined supplementation effectively enhanced protein, carbohydrate, lipid and mineral metabolism in the bulls.